Negotiations on the Global Goal on Adaptation (GGA): State of play and opportunities for farmers to engage - Njuguna, Lucy Wanjiku (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This presentation provides an overview of the current state of negotiations on the Global Goal on Adaptation (GGA), highlighting key progress made under the UNFCCC, particularly through the Glasgow–Sharm el-Sheikh work programme and the UAE-Belem work programme on indicators. The presentation is designed to help stakeholders identify entry points and contribute to discussions on the GGA.